189k views
5 votes
Select the correct answer from each drop-down menu.

When p2 – 4p is subtracted from p2 + p – 6, the result is . To get p – 9, subtract from this result.

User Woong
by
4.8k points

1 Answer

5 votes

p2 – 4p is subtracted from p2 + p – 6 can be written as:

(p² + p – 6)-(p²– 4p)

=p²+p-6-p²+4p

=(p²-p²)+(p+4p)-6 Grouping the like terms.

=0+5p-6 Combining the like terms.

=5p-6

Now the question is to subtract p-9 from the above result 5p-6.So,

(5p-6)-(p-9)

=5p-6-p+9

=(5p-p)+(9-6)

=4p+3

Hence, the answer is 4p+3.

User Muhmuhten
by
5.6k points